Engineering nanoparticles to overcome the mucus barrier for drug delivery: Design, evaluation and state-of-the-art - Chang Liu (Elsevier, 2021)
Mucus is a viscoelastic hydrogel that lubricates and protects mucosal tissues such as the eyes, lung, gastrointestinal tract, and vagina. Nanoparticle-based drug delivery systems (DDSs) can be easily trapped in the mucus network by steric obstruction and/or binding interactions and then are efficiently cleared away with rapid mucus turnover, thereby limiting mucosal drug delivery efficacy. Modulating the physicochemical properties of nanoparticles (NPs), including size, surface hydrophilicity and charge, shape, and rigidity, is an effective method to overcome the mucus barrier. This review first describes the protective barrier properties of mucus and how mucus affects the fate of NPs. It then reviews the techniques for evaluating particle movement in mucus, including macroscopic diffusivity and microcosmic diffusion mechanisms. The state-of-the-art strategies exploited by researchers to overcome the mucus barrier by using NPs are discussed. Finally, the dilemma and solutions of balancing both mucus penetration and cellular uptake barriers are discussed.